(untitled) (Al-Mansour Journal, 2023)
The research includes the point of view over the need to apply alternative penalties of the short period imprison as a punishment , to decrease the negative effects which emerge as a result to the application to the short period imprison . The research will be a study between Iraqi penal code and some Arab and foreign penal codes . The research aims to study the determination of the conception of the alternative penalties and to emerge the impotence of these penalties . and then the clarification of the way in Iraq . The researcher asserts on the necessity of existence of a model of an Arab code project including the definition of these penalties and the manners which help to apply them instead of the imprison punishment .